Association Between Nutrient Intake and Anthropometric Indices of Female and Male Respondents in North West Region, Cameroon - Ange, Ebai Nee Besong Patricia; Manga, Eyenga; Mabiama, Gustave; Isabelle, Bouelet Ntsama; Fernande, Nyangono Biyegue (British Journal of Healthcare and Medical Research, 2024)
This study examined the association between nutrient intake and anthropometric indices of female and respondents in rural and urban North West Region of Cameroon. Multi-stage random sampling was used to select 480 households. Ethical approval/informed consent were obtained. Structured questionnaires, dietary assessments and focus group discussions provided information on household food consumption pattern and food security. Descriptive of simple percentages mean and standard deviation and inferential statistics of Pearson product moment correlation coefficient were used to analyze collected data and significance at p<0.05 accepted. Data obtained and analyzed showed that, energy correlates with height and weight in IYC 6-54 months while protein correlates with weight in females 24-59 months of age in rural households. Also energy correlates with height and weight while protein correlates with weight in females 6-9 years of age in rural households. In females 10-19 years, energy and protein correlates with height and weight in rural households while energy and protein correlates with height and weight in males 6-9 years of age in rural households while energy correlates with weight and height in males 10-19years in rural and urban households. No correlation was observed in adults 20 years and above as observed.